2011
DOI: 10.1007/s00018-011-0706-6
|View full text |Cite
|
Sign up to set email alerts
|

γδ T-APCs: a novel tool for immunotherapy?

Abstract: The series of seminal articles in this book clearly illustrate the multi-functional nature of γδ T cells. Some of the functions correlate with the tissue tropism of distinct γδ T cell subsets whereas others appear to result from oligoclonal selection. Here, we discuss the antigen-presenting cell (APC) function of the major subset of circulating γδ T cells, Vγ9/Vδ2 T cells, present in human blood. During tissue culture, Vγ9/Vδ2 T cells uniformly respond to a class of non-peptide antigens, so-called prenyl pyrop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
46
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 72 publications
(48 citation statements)
references
References 70 publications
2
46
0
Order By: Relevance
“…29 Both classic MHC I and MHC II loading pathways are therefore present in gd T cells. 30 Even though gd T cells predominantly exert innate-like responses, they are able to transform into memory cells. Thus na€ ıve (CD45RA C CD27 C ) and central memory (CD45RA ¡ CD27 C ) gd T cells will home to secondary lymphoid organs, while effector memory (CD45RA ¡ CD27 ¡ ) and terminally differentiated (CD45RA C CD27 ¡ ) gd T cells show immediate effector functions on inflammatory sites.…”
Section: Gd T Cells and Cancer Immunitymentioning
confidence: 99%
“…29 Both classic MHC I and MHC II loading pathways are therefore present in gd T cells. 30 Even though gd T cells predominantly exert innate-like responses, they are able to transform into memory cells. Thus na€ ıve (CD45RA C CD27 C ) and central memory (CD45RA ¡ CD27 C ) gd T cells will home to secondary lymphoid organs, while effector memory (CD45RA ¡ CD27 ¡ ) and terminally differentiated (CD45RA C CD27 ¡ ) gd T cells show immediate effector functions on inflammatory sites.…”
Section: Gd T Cells and Cancer Immunitymentioning
confidence: 99%
“…While such a role can only be postulated in humans and at best supported by indirect epidemiological evidence, infection and/or vaccination experiments in non-human primates might address the contribution of Vg9/Vd2 T cells to the generation of high-affinity, class-switched antibodies. Such studies could exploit the availability of convenient pathogen models such as specially engineered HMB-PP-deficient strains of Listeria monocytogenes [45] or HMB-PP overproducing strains of Mycobacterium tuberculosis [46].Recent findings also point towards a more antigen-restricted role of Vg9/Vd2 T cells in providing B-cell help, given their potential to take up exogenous antigens and present them to CD4 1 and CD8 1 T cells [33,47]. Antigen-presenting gd T cells may thus be able to interact directly with T FH cells.…”
mentioning
confidence: 99%
“…Recent findings also point towards a more antigen-restricted role of Vg9/Vd2 T cells in providing B-cell help, given their potential to take up exogenous antigens and present them to CD4 1 and CD8 1 T cells [33,47]. Antigen-presenting gd T cells may thus be able to interact directly with T FH cells.…”
mentioning
confidence: 99%
“…In addition to their direct anti-infection activities, human cd-T cells act as professional APCs and take up, process and present pathogen-related antigens from both free viral particles 29 and infected cells 57,105 to other effector immune cells. 106,107 These cd-T APCs express approximately similar levels of HLA-DR and CD80/ CD86 compared to traditional APCs 29 and induce NK cell activation, 108,109 antigen-specific ab-T-cell responses 29,107 and even antibody production. 67 Although the physiological roles of cd-T APCs still need to be illuminated by more in vivo studies, recent investigations of murine cd-T cells have confirmed the general existence of cd-T APCs.…”
Section: Direct Anti-infection Activity Mediated By Cd-t Cells Directmentioning
confidence: 99%